Tasawuf dan Psikologi Islam - Achmad Mubarok (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
This text explores psychology as part of the implicit message within the teachings of Islam. However, the psychological insights present in the Qur'an have not received serious attention. As a scientific discipline, psychology was only recognized in the late 18th century, but its roots can be traced back to the time of Plato. As a modern science, psychology has advanced significantly. The concept of “Nafs” (soul), which is a crucial aspect of psychological analysis, is mentioned over three hundred times in the Qur'an and Hadith, yet a horizontally oriented psychology did not emerge in the classical Islamic scholarly tradition. Scholars tended to discuss it more from the perspectives of ethics and Sufism, which are more vertically oriented. It was only in the 1950s that Muslim intellectuals, who studied in the West, began to show interest in the study of psychology. Furthermore, there have been efforts to offer alternative concepts of psychology, namely psychology from an Islamic perspective.